The derivative condition, an aesthetics of resolution, and the figure of the renegade: A conversation - Gerald Nestler; Christian Kloeckner; Stefanie Mueller (Finance and Society, 2018)
The work of the artist and writer Gerald Nestler explores finance and its social implications since the mid-1990s. Based on his professional experience as a trader as well as on post- disciplinary research, he has developed a unique approach that brings together theory and conversation with installation, video, performance, text, and other art forms. Probing into the narrative structures of contemporary capitalism, Nestler offers a techno-political critique directly from the core of the financial markets. This interview addresses his reading of the derivative as a world-producing apparatus that shapes the experience of the present by preconfiguring the future, and that provokes a shift from representational to performative speech in the actualization of biopower based on the exploitation of volatility and leverage. In conversation with Christian Kloeckner and Stefanie Mueller, he argues for the formation of specific human/non-human alliances that directly attack algorithmic as well as socio- economic black-boxing (schemes that monopolize inherently non-scarce resources), so as to open our imagination to skills and tactics that would allow us to navigate the rich but volatile flows of social, political, and economic abundance.
Keywords: 300; Art; resolution; renegade; derivatives; volatility; leverage